Pengaruh Pemberdayaan Karyawan dan Lingkungan Kerja Terhadap Kinerja Karyawan dengan Produktivitas Kerja Sebagai Variabel Mediasi pada UMKM di Madura - Maudina Alia; Helmi Buyung Aulia Safrizal (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to explore and analyze the influence of employee empowerment and work environment on employee performance in Micro, Small, and Medium Enterprises (MSMEs), with work productivity as a mediating variable. In the context of MSMEs, employee empowerment and work environment are considered important factors that can affect employee performance. Employee empowerment involves giving authority, autonomy, and opportunities to develop, while the work environment includes physical and psychological aspects that affect work comfort and effectiveness. This study uses a quantitative method with a survey on MSMEs in Madura Island, and involves data collection through questionnaires filled out by employees and managers. Data collected as many as 103 samples will be analyzed using the smartPLS 4.0 technique to test the relationship between employee empowerment, work environment, work productivity, and employee performance. The results of the study indicate that employee empowerment does not significantly affect employee performance, employee empowerment significantly affects work productivity, work environment significantly affects employee performance, work environment significantly does not affect work productivity, work productivity significantly does not affect employee performance in MSMEs in Madura Island. These findings provide important insights for MSME owners and managers in designing empowerment strategies and creating a supportive work environment. By increasing employee empowerment and creating a conducive work environment, MSMEs can improve overall employee productivity and performance. This study suggests that MSMEs should pay more attention to these factors in an effort to improve their competitiveness and business success.